Transcription, Inheritance, and Meaning of Tri Sandya Puja Mantra - Ni Made Ayu Dwara Putri; Ni Wayan Ardini; I Wayan Rai S (Journal of Aesthetics, Creativity and Art Management, 2023)
Tri Sandya Puja is a mantra (prayer) that is routinely performed three times a day by Hindus in Bali. Derived from two words, namely Tri which means "three" and Sandya which means "relationship". Tri Sandya is three times to connect with God (Ida Sang Hyang Widhi Wasa). It is a chant of a mantra and is categorized as an oral literature in the form of magical poetry. The Tri Sandya Mantra has been passed down orally in Bali and consists of six stanzas. In this article the authors will discuss the Tri Sandya Puja in more detail in terms of the meaning of the mantra, transcription of the melody of the mantra as well as cultural inheritance and its existence to date.